Psychological Aspects of E-Learning: Face Perception (Theoretical-Experimental Research) - Mikhail MATVEEV (Communications of International Proceedings, 2021)
Today, due to the COVID-19 pandemic, all educational institutions have to switch from the traditional forms of education to e-learning. Some researchers say that the Internet has radically changed the way today’s young people learn and communicate. That is why it essential to ask ourselves how we can use the power of web and multimedia technologies to improve the quality of university education. The purpose of this article is to study the perception of information received during e-lessons and e-conferences when participants can see only faces of each other. We studied verbal and non-verbal components of multimodal texts describing human faces, which will also cast the light on the non-verbal foundations of cognitive processes. The results of our experiment show that face perception is an important element of e-learning as it often substitutes all other types of non-verbal communication between students and teachers, and, at the same time, we proved that it is of importance in the education process. It is not only the verbal component of communication that conveys information to students but also its non-verbal components, i.e. the verbal part of the message is supplemented and sometimes perceived radically differently under the influence of extra-linguistic factors. The purpose of this article is to study the perception of information received during e-lessons and e-conferences when participants can see only faces of each other.  That is why we studied verbal and non-verbal components of multimodal texts describing human faces, which will also cast the light on the non-verbal foundations of cognitive processes. Why did we choose images of human faces? The perception of persons has been studied by various sciences for a long time because it is believed that this will help to better understand the various aspects of human development. A person’s face is very different from other stimuli because it has several characteristics.